ANALYSIS OF SELF-ESTEEM OF YOUNG PEOPLE ON THE INTERNET AND SOCIAL NETWORKS (Multidisciplinary Journal of Science and Technology, 2025)
This article investigates the relationship between the self-esteem of young people and their experiences on the Internet, particularly within social networks. The rapid growth of digital communication has transformed the way adolescents and young adults construct identity, build social relationships, and evaluate themselves. While online platforms provide opportunities for self-expression, connection, and support, they also expose young users to risks such as comparison, cyberbullying, and dependence on external validation. This psychological analysis highlights the dual impact of social networks on self-esteem, exploring both positive and negative mechanisms.